(Salen)Mn(iii)-catalyzed chemoselective acylazidation of olefins. Issue 28 (27th June 2018) - Zhang, Liang; Liu, Shuya; Zhao, Zhiguo; Su, Hongmei; Hao, Jingcheng; Wang, Yao
Abstract : A (salen)Mn(iii )-catalyzed chemoselective acylazidation of olefins was developed based on strategic application of the distinct reactivity of oxomanganese(v ) species. Abstract : We describe a (salen)Mn(iii )-catalyzed three-component reaction of aldehydes, olefins, and sodium azide for the installation of two useful groups (CO and N3 ) into the double bond. Traditionally, (salen)Mn(iii ) in conjunction with iodosobenzene is a classical catalysis system for epoxidation of olefins. Owing to the highly competitive oxygenation approaches, it is a true challenge to establish a distinct strategy for the exploration of new olefin transformations based on this (salen)Mn(iii ) catalysis system. Herein, the key to this (salen)Mn(iii )-catalyzed acylazidation of olefins was the rational application of the distinct reactivity of oxomanganese(v ) species which is capable of abstracting a hydrogen atom from a substrate C–H bond. This chemoselective reaction occurred in a precisely designed reaction sequence and tolerates complex molecular structures.